ANALISIS GAMBAR STIMULUS PADA PERMULAAN BAB BUKU AJAR PAI KELAS VIII PRESPEKTIF VISUAL DAN PENDIDIKAN - Inayati, Nurul; Masithoh, Arina Dewi (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2024)
Analysis of stimulus images at the beginning of the 8th grade Islamic Religious Education (PAI) textbook chapter highlights the important role of visuals in the context of religious learning. This research adopts a qualitative perspective with a focus on content, semiotic, and visual analysis to understand how these images influence students' perceptions and facilitate deep learning. Through this approach, we reveal the various messages, themes and values ​​implicit in these images, as well as how visual elements such as composition, color and symbolism are used to convey Islamic religious concepts. The results of this research provide valuable insight into the potential of stimulus images as an effective tool in enriching students' learning experiences in religious subjects, as well as highlighting the importance of integrating visual aspects in the religious education process. The practical implications of these findings can enrich PAI learning designs that are more responsive to students' needs and preferences in visual contexts.